R.C. Beams Strengthening by Carbon Fiber Reinforced Polymer Against Two Points Load Divergence - Zohair Yousif, Mohammad (Journal of Engineering and Sustainable Development, 2012)
The results of an experimental study of the behavior of the beams strengthened with Carbon Fiber Reinforced Polymer (CFRP) sheets with the load divergence are presented. 100x100x100 mm CFRP sheets are epoxy bonded in U shape around the tension face and web of concrete beams to enhance their ductility and strengths. The effect of CFRP sheets on strength and stiffness of the beams is considered for various lengths of the CFRP with respect to the distance from the center of beams, which are increased according to the distance between the two points load. Six beams were fabricated, strengthened with CFRP systems (6 different lengths). The beams were loaded to failure. Different mode of failure and gain in ultimate strength were observed, depending on the length of the Carbon Fiber.